Serum levels of ischemia modified albumin in overweight/obese postmenopausal women: a potential biomarker of atherosclerotic burden associated with oxidative stress. - Kazanis, Konstantinos; Dalamaga, Maria; Kassi, Eva; Nounopoulos, Charalampos; Manolis, Antonios S; Merantzi, Georgia; Jullien, Gerard; Dionyssiou-Asteriou, Amalia (Maturitas, 2011)
OBJECTIVE: Menopause is associated with weight gain and an increase of cardiovascular risk. The aim of the present study was to estimate serum ischemia-modified albumin (IMA) levels in postmenopausal women and evaluate their association with body mass index (BMI) and coronary artery disease (CAD). METHODS: The study included 130 non-smoker postmenopausal women aged 43-80: 40 with BMI 26-32 kg/m(2) (Group A), 60 with BMI 21-25 kg/m(2) (Group B), and 30 with documented CAD and BMI 23-29 kg/m(2) (Group C). Serum IMA, albumin, hsCRP and NT-proBNP, glucose and insulin were measured. Homeostasis assessment model score (HOMA) and Quantitative insulin sensitivity index (QUICKI) were co-estimated. RESULTS: Serum IMA and IMA to albumin ratio were significantly elevated in Group A as compared to Group B (p<0.001) and similar to those of Group C. hsCRP and NT-proBNP did not differ between Groups A and B while they were lower in comparison to Group C (p<0.001). Glucose, insulin and HOMA were elevated in Group A compared to Group B (p<0.001) while QUICKI was lower (p<0.001). In Group A, IMA was positively correlated with BMI, hsCRP, insulin, HOMA and negatively with QUICKI. In postmenopausal women, multivariable regression analysis revealed that obesity was the strongest significant determinant of circulating IMA levels (p<0.001) contributing, therefore, to the elevated serum IMA concentration. CONCLUSIONS: Postmenopausal obesity is associated with elevated serum IMA possibly due to obesity associated oxidative stress. IMA measurement could provide an assessment of atherosclerotic burden in postmenopausal women. Further clinical evaluation is under investigation.
Keywords: Adult; Aged; Aged, 80 and over; Atherosclerosis; Biomarkers; Blood Glucose; Body Mass Index; C-Reactive Protein; Coronary artery disease; Female; Humans; Insulin; Insulin Resistance; Middle Aged; Multivariate Analysis; Natriuretic Peptide, Brain; Obesity; Oxidative Stress; Peptide Fragments; POSTMENOPAUSE; Serum albumin